Biomarkers for demographic research: sperm counts and other male infertility biomarkers. (2nd January 2020) - Westerman, Ronny
ABSTRACT: Some male infertility biomarkers are etiologically linked to idiopathic infertility in men, the direct cause of which often cannot be determined with conventional sperm count parameters. Open questions remain regarding the universal and generic infertility definitions that cover and combine the clinical, epidemiological, and demographic perspectives. The main effort in the application of these infertility biomarkers are accounted by more or less strict discrimination criteria. For male infertility, beyond classical sperm count assessments, the DNA fragmentation index (DFI) is an adequate biomarker. DFI strongly correlates with pregnancy rates and even strict discrimination criteria for infertility outcomes. Other common biomarkers are reactive oxygen species (ROS) and antisperm antibodies (ASAs), which can explain some biomedical infertility disorders within major constraints. More frequently applied in demographic research, telomere length component analysis is based on identifying the genetic impact of cellular longevity. Sperm telomere length is becoming established as a potential biomarker in infertility research. The aim of this review is to provide an overview of the current status and limitations to the application of novel biomarkers, including TEX101, for infertility research. The review also discusses potential options for the use of biomarkers in population-based studies. Abbreviations : ASAs: antisperm antibodies; DFI: DNA fragmentation index; DNA: deoxyribonucleic acid; ECM1: extracellular matrix protein 1; FSH: follicle stimulating hormone; HS: hypospermatogenesis: IVF: in vitro fertilization; LDHC: L-lactata dehydrogenase C chain; MA: maturation arrest; microTESE: microdissection testicular sperm extraction; NOA: nonobstructive azoospermia; NP: nonprogressive; OA: obstructive azoospermia; pH: potential Hyrogenii (pH-value); PR: progressive; PTGDS: prostaglandin D synthese; ROS: reactive oxygen species; SA: semen analysis; SCO: sertoli cell only; SCSA: sperm chromatin structure assay (SCSA); TL: telomere length; TESE: testicular sperm extraction; TEX101: a glycoprotein that belongs to Ly6/urokinase type plasminogen activator receptor-like protein (uPAR)(LU) superfamily, to be a germ-cell-specific molecular sperm extraction; TUNEL: terminal deoxnucleotidyl dispersion tranferase dUTP nick-end labeling; WHO: World Health Organization